2003
DOI: 10.4141/a02-077
|View full text |Cite
|
Sign up to set email alerts
|

Responses of the bovine mammary glands to absorptive supply of single amino acids

Abstract: Responses of the bovine mammary glands to absorptive supply of single amino acids. Can. J. Anim. Sci. 83: [341][342][343][344][345][346][347][348][349][350][351][352][353][354][355]. In this review, we discuss the mechanisms of responses of various tissues of the lactating dairy cow, particularly the mammary glands, to perturbations in supply of single amino acids that result in observed milk protein yields. Additions of methionine, lysine, histidine or leucine to the absorptive supply cause arterial concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 100 publications
(112 reference statements)
4
43
2
Order By: Relevance
“…If indeed endogenous proteins are the main source of energy substrates in the heat-stressed cow, then it is possible that EAA, which would normally be destined for milk protein synthesis, are also being scavenged for gluconeogenic purposes, reducing the precursor pool for the synthesis of milk proteins. The reduced milk protein concentration that we observed in heat-stressed cows (33.1 g/L, in contrast to 34.6 g/L in TN-AL) may indicate an imbalance of EAA as characterized by Cant et al (2003).…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…If indeed endogenous proteins are the main source of energy substrates in the heat-stressed cow, then it is possible that EAA, which would normally be destined for milk protein synthesis, are also being scavenged for gluconeogenic purposes, reducing the precursor pool for the synthesis of milk proteins. The reduced milk protein concentration that we observed in heat-stressed cows (33.1 g/L, in contrast to 34.6 g/L in TN-AL) may indicate an imbalance of EAA as characterized by Cant et al (2003).…”
Section: Discussioncontrasting
confidence: 78%
“…The yield of milk protein has a low sensitivity to concentrations of single precursor AA and it may be that the utilization of AA for milk protein synthesis is fixed (Cant et al, 2003). As our results have shown that circulating plasma total protein concentrations are unaffected by heat stress, it may be that it is not delivery of AA precursors to the mammary epithelium that is changing milk protein composition under heat stress, but rather elements of the biosynthetic pathway (transcription/translation).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Predicting the magnitude of the milk protein response, however, has proven difficult. In the lactating dairy cow, for which protein nutrition and milk protein yield carry economic weight, the limiting EAA concept, where the supply of one EAA can prevent responses to all other EAA, does not appear to hold Cant et al, 2003). Recently, researchers have investigated the potential role of regulation of mammary mRNA translation in the response of milk protein yield to nutrition of the dam.…”
Section: Introductionmentioning
confidence: 97%
“…However, canola meal is not an effective source of protein for high-producing dairy cows because of its high effective ruminal protein degradability, which ranges from 44.3% to 74% (Wright et al, 2005). Modern high producing and rapidly growing ruminants require protein in excess of ruminal microbial synthesis, where the supply of microbial protein cannot meet requirements for metabolizable protein (Waltz and Stern, 1989;Cant et al, 2003). It is essential that the diet contains slowly degrading proteins with a high potential for rumen escape.…”
Section: Introductionmentioning
confidence: 99%